Making Organic Fertilizer Based on JADAM Natural Farming with Local Adaptation - Alimi, Moh. Yasir; Akhiroh, Ninuk Sholikhah; Fajar, Fajar; Arsi, Antari Ayuning (Komunitas: International Journal of Indonesian Society and Culture, 2024)
JADAM is an organic farming method that has been proven to empower farmers, not only allowing farmers to make their own fertilizers and pesticides, but also returning farmers to become experts in agriculture and their own land because of the experiments and introduction of biological potential in the environment they observe. The purpose of this article is to develop a JADAM model that is adjusted to the availability of materials in the surrounding environment. It is done under the concept of organic farming, and community empowerment. This article is developed from the results of a community service activities. The findings of the research show that there are three ways of making organic fertilizer from materials found the surrounding, namely household organic waste, leaf shoots, and a combination of waste to make organic NPK. Another interesting development of the JADAM method is an organic fertilizer that can be drunk, made from fruits and vegetables. It proves that organic fertilizer is more than safe so that it can be drunk.